THE OVERVIEW OF STUDENTS FACULTY OF NURSING PADJADJARAN UNIVERSITY ATTITUDE TOWARDS FREE SEX BEHAVIOR - Zihan Rahminabillah; Suryani Suryani; Nita Fitria (Journal of Maternity Care and Reproductive Health, 2020)
Students in the university level have developmental tasks to receive and to give love, that was developed in tying relationships with the opposite sex and manifested in sexual behavior. In Jatinangor generally college students have had sexual activities with their sexual partner such as kissing, necking, petting, and intercourse. This phenomenon needed to get special attention from various parties so it would not adverse impact the students and their surroundings. This study aimed to find out the overview of students of faculty of nursing padjadjaran university attitude towards free sex behavior. The method used in this study was descriptive quantitative with the number of the respondents 240 students that was taken with stratified random sampling technique, continued by proportional sampling method. Respondents who were involved in this study were regular faculty of nursing students batch 2013, 2014, 2015, and 2016. Data collected by questionnaire using likert scale, and analyzed by distribution frequency. The results were divided into 2 i.e. Favorable with the score T ≥ 50 and Unfavorable with the score T <50.The result of this study indicated that as much as 128 students (53,3%) have Unfavorable attitude towards free sex behavior and as much as 112 students (46,7%) have Favorable attitude towards free sex behavior.Conclusions from the result of this study can be concluded that most of the students have Unfavorable attitude toward free sex. To maintain that result, required involvement of various parties especially the faculty. The faculty’s guidance and counseling team was expected to be able to do the right approach to the students and innovate in educating the danger of free sex from various perspective.